Afrofuturism and Indigenous Futurism are Democracy: STEM Possibilities for (Re)Humanizing Pedagogy in Education - Harris, Tiffany (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2025)
How can STEM education benefit from a paradigm shift, beyond economic growth and citizenship development, towards alternative perspectives for problem-solving to combat anthropogenic dilemmas? This conceptual essay investigates why we should incorporate Afrofuturism and Indigenous Futurism into STEM education to expand possibilities for more humanizing pedagogy and praxis. I argue STEM innovation has been at the forefront of enacting democracy in the United States. First, I provide a critical examination of STEM, during the colonial era and Early Republic period, by reframing goals of U.S. democracy as being closely aligned with technological innovation. The entry point is late 20th century and early 21st century educational reform and then shifts to scrutinize land extraction tactics and the institution of schooling during the 18th and 19th centuries. Next, I concentrate on how 20th century societal STEM trends influence curriculum as well as normalized beliefs about STEM fields. Lastly, I advocate for Afrofuturism and Indigenous Futurism as nuanced extensions of art-integration into STEM. By centering Afrofuturism and Indigenous Futurism in 21st century STEM education and research, we can better actualize U.S. democratic ideals oriented toward valuing whole persons, especially concerning the Anthropocene.